2015
DOI: 10.2139/ssrn.3079250
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Models, Heterogeneity of Initial Assets, and Wealth Inequality

Abstract: Life cycle general equilibrium models with heterogeneous agents have a very hard time reproducing the American wealth distribution. A common assumption made in this literature is that all young adults enter the economy with no initial assets. In this article, we relax this assumption -not supported by the data -and evaluate the ability of an otherwise standard life cycle model to account for the U.S. wealth inequality. The new feature of the model is that agents enter the economy with assets drawn from an init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Another common way to deal with negative incomes is to set them to zero. Many researchers (Burkhauser & Simon, 2010;de Battisti et al, 2019;Feng et al, 2006;Ferreira & Gomes, 2015;OECD, 2017) applied this truncation of data with negative values. The truncation can lead to a loss of information, but studies from Seidl et al (2012) and Bray (2014) showed consistency in the results setting negative values to zero.…”
Section: The Portfolio Of Income Generating Activities: Income Calcul...mentioning
confidence: 99%
“…Another common way to deal with negative incomes is to set them to zero. Many researchers (Burkhauser & Simon, 2010;de Battisti et al, 2019;Feng et al, 2006;Ferreira & Gomes, 2015;OECD, 2017) applied this truncation of data with negative values. The truncation can lead to a loss of information, but studies from Seidl et al (2012) and Bray (2014) showed consistency in the results setting negative values to zero.…”
Section: The Portfolio Of Income Generating Activities: Income Calcul...mentioning
confidence: 99%